2020
DOI: 10.1002/ppsc.201900462
|View full text |Cite
|
Sign up to set email alerts
|

Monodispersed β‐Glycerophosphate‐Decorated Bioactive Glass Nanoparticles Reinforce Osteogenic Differentiation of Adipose Stem Cells and Bone Regeneration In Vivo

Abstract: Design and development of highly bioactive nanoscale biomaterials with enhanced osteogenic differentiation on adipose stem cells is rather important for bone regeneration and attracting much attention. Herein, monodispersed glycerophosphate‐decorated bioactive glass nanoparticles (BGN@GP) are designed and their effect is investigated on the osteogenic differentiation of adipose mesenchymal stem cells (ADMSCs) and in vivo bone regeneration. The surface‐modified BGN@GP can be efficiently taken by ADMSCs and show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…In a study conducted by Guo et al., in vivo animal experiment of glycerophosphate‐decorated BG nanoparticles (BGN@GP) was clarified. According to the results of histological investigations, it was observed that BGN@GP has a high capacity in bone regeneration 97 . Moreover, in a study on the biological properties of polyelectrolyte multilayer coatings incorporated with silver/strontium containing mesoporous BG on 316L stainless steel, favorable angiogenesis, and bone regeneration properties were demonstrated based on H&E results 98 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study conducted by Guo et al., in vivo animal experiment of glycerophosphate‐decorated BG nanoparticles (BGN@GP) was clarified. According to the results of histological investigations, it was observed that BGN@GP has a high capacity in bone regeneration 97 . Moreover, in a study on the biological properties of polyelectrolyte multilayer coatings incorporated with silver/strontium containing mesoporous BG on 316L stainless steel, favorable angiogenesis, and bone regeneration properties were demonstrated based on H&E results 98 .…”
Section: Resultsmentioning
confidence: 99%
“…According to the results of histological investigations, it was observed that BGN@GP has a high capacity in bone regeneration. 97 Moreover, in a study on the biological properties of polyelectrolyte multilayer coatings incorporated with silver/strontium containing mesoporous BG on 316L stainless steel, favorable angiogenesis, and bone regeneration properties were demonstrated based on H&E results. 98 Hence, the synergistic effect of BG and AV has a significant role in repairing the defect area in this study.…”
Section: 6mentioning
confidence: 99%
“…Therefore, the physiological stability of BGN should be ameliorated to maximize its applications in bioimaging and cancer therapy. Recently, our group found that the physiological stability, in vivo degradation, and osteogenic activity of BGN could be augmented through decorating β-glycerol phosphate disodium on BGN (BGN@GP). , Unfortunately, the BGN@GP does not possess the cancer cell targeting ability and fast release of GP, which was not suitable for targeted cancer imaging and therapy. In addition, the photoluminescent Eu-doped BGN (EuBGN) was also developed for drug delivery and cell imaging.…”
Section: Introductionmentioning
confidence: 99%
“…Bioactive glass nanoparticles (BGN) with a controllable nanostructure, good biodegradability, simple synthesis process, and low cost were rendered attractive for biomedical applications including drug and gene delivery, tumor therapy, and tissue repair. Previously, our group has developed multifunctional BGN for promising applications including gene delivery, bone regeneration, bioimaging, skin repair, and tumor therapy. The multifunctional BGN with efficient tumor therapy and bone regeneration were also reported through the assembly with dopamine . Molybdenum (Mo) is an important trace element in the human body, and it possesses a variety of biological effects on different tissues, such as detoxification, iron transport, intellectual development, and metabolism. In addition, Mo is a typical variable valence element that could show properties of Mo 6+ and Mo 4+ .…”
mentioning
confidence: 99%